2020
DOI: 10.1007/s10750-020-04425-5
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of fish eggs and larvae in a cascade of small hydropower plants with fish ladders

Abstract: This study was conducted to investigate fish eggs and larvae dispersal in a river stretch influenced by small hydropower plants in Southeast Brazil. The main hypothesis is that the downstream dispersal of free-flowing eggs and larvae is likely to occur given the small size of the studied reservoirs and that passage through the dam may occur, with the fish ladder contributing to it. Eggs and larvae were collected fortnightly, between November 2016 and February 2017, from locations upstream of two dams, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…On the contrary, the frequency of fish eggs and larvae sampled in the surface sampling may be attributed to the greater presence of pelagic eggs and the turbidity of the sampled rivers. Recent studies have suggested that precipitation and turbidity are the main triggers for spawning, which provide higher densities of fish eggs and larvae under these conditions (Brambilla et al ., 2022; Lopes et al ., 2019; Makrakis et al ., 2022). Furthermore, it is known that the presence of eggs may be the result of past events ( i.e ., 1–3 days earlier; see Nakatani et al ., 2001); consequently, the density of eggs may be attributed to the time from development to hatching and not only to the spawning time.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the frequency of fish eggs and larvae sampled in the surface sampling may be attributed to the greater presence of pelagic eggs and the turbidity of the sampled rivers. Recent studies have suggested that precipitation and turbidity are the main triggers for spawning, which provide higher densities of fish eggs and larvae under these conditions (Brambilla et al ., 2022; Lopes et al ., 2019; Makrakis et al ., 2022). Furthermore, it is known that the presence of eggs may be the result of past events ( i.e ., 1–3 days earlier; see Nakatani et al ., 2001); consequently, the density of eggs may be attributed to the time from development to hatching and not only to the spawning time.…”
Section: Discussionmentioning
confidence: 99%
“…One potential issue with the use of fishways as a management tool for Neotropical species is that, by enabling fish to reach spawning grounds upstream of reservoirs (even though suitable spawning grounds may be available downstream of dams), their eggs and larvae may suffer high mortality as they drift downstream through the dam created lentic environment and/or move through turbines or spillway intakes (Pelicice et al, 2015;Boys et al, 2016). Brambilla et al (2021) studied the downstream dispersal of fish eggs and larvae through reservoirs created by small hydropower facilities to determine which factors influence their drift and whether downstream passage through fishways can occur. The authors regularly sampled larvae and eggs from the riverine, transition and lentic zones of two small reservoirs as well as in the fishways associated with the dams forming the reservoirs.…”
Section: Lessons From Brazilmentioning
confidence: 99%
“…Considered together, the papers in this issue point to a series of important conclusions regarding the sustainability of hydropower and the ways in which it can be made and maintained as environmentally friendly as possible. Technology and technological change emerging from environmental studies have important roles to play, in the context of providing researchers with new tools to understand the nuances of fish ecology, such as downstream larval dispersal (Brambilla et al, 2021), and fish interactions with hydropower facilities (Hahn et al, 2021). New hydropower engineering technologies will be similarly important for understanding how hydropower operational regimes may be adjusted to account for fish behaviour in ways that will reduce overall mortality (Smokorowski, 2021;Stenberg et al, 2021;Tuononen, et al, 2021).…”
Section: Synopsismentioning
confidence: 99%
“…In South American rivers, the first studies on ichthyoplankton transport were carried out in the Solimões and Amazonas rivers (Araujo‐Lima & Oliveira, 1998), and in the Paraná River (Baumgartner et al, 2004; Bialetzki et al, 1999). Currently, studies evaluating fish reproduction behaviour and dynamics have been conducted in several river basins with a focus on assessing the ichthyoplankton drift pattern related to the impact of hydroelectric plants (Barthem et al, 2014; Brambilla et al, 2020; Da Silva et al, 2020; Fuentes et al, 2016; Garcia et al, 2018; Mounic‐Silva et al, 2019; Suzuki et al, 2013). And the free‐flowing rivers, especially dam‐free tributaries, has been an appeal for the conservation of fish species (Da Silva et al, 2015, 2019; Makrakis et al, 2019; Marques et al, 2018; Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%